Security and data reliability in cooperative wireless networks - Hassan, Emad S. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2018)
Following a detailed overview of cooperative communications and the physical layer security, this book proposes relay and jammer selection schemes for security in one-way cooperative networks and to improve physical layer security in two-way cooperative networks. It also proposes a Cooperative Hybrid Self-Healing scheme to enhance the confidentiality of the data collected by UWSN. It ends with a proposal called Self-Healing Cluster Controlled Mobility (SH-CCM) scheme based on hybrid cooperation between both Proactive and Reactive peers and the sick sensors at both network and cluster levels to guarantee the security in UWSN--
Includes bibliographical references and index.
Keywords: Wireless sensor networks -- Reliability; Cooperating objects (Computer systems) -- Reliability; Wireless sensor networks -- Security measures; Cooperating objects (Computer systems) -- Security measures